Design, synthesis and biological evaluation of novel biphenylsulfonamide derivatives as selective AT2 receptor antagonists - Wang, Danhui; Zhao, Wenjie; Zhang, Zuzhi; Zhang, Yanchun; Li, Jiaming; Huang, Weijun (Frontiers in Chemistry, 2022)
A novel series of benzenesulfonamide derivatives that selectively act on the AT2 receptor have been designed and synthesized. The binding affinity and functional activity were evaluated by radio-ligand binding analysis and cell neurite outgrowth assay, respectively. The compounds 8d, 8h, 8i, 8j, 8l, and 9h exhibited moderate selectivity and affinity for the AT2 receptor. Among them, 8j exhibited agonist activity and 8l displayed similar selectivity to the AT2 receptor with PD123,319. Molecular docking was carried out to analyze the binding mode and binding site between the compound and the AT2 receptor to provide a reference for further development.